Feed‐based common carp farming and eutrophication: is there a reason for concern?. (26th December 2019) - Roy, Koushik; Vrba, Jaroslav; Kaushik, Sadasivam J.; Mraz, Jan
Abstract: Metadata from 70 research articles on Cyprinus carpio digestibility published between 1973 and 2017, covering 71 feed ingredients, were analysed. Interquartile range (IR) of nitrogen (N) and phosphorus (P) content in feedstuffs was 5–8% and 0.7–1.2% of dry matter, respectively, with digestible N:P 7.2:1–44.1:1. IR of N digestibility (79–99%) was high, whereas IR of P digestibility (27–47%) was rather poor. Dietary energy digestibility (gross energy and non‐protein energy) was >76%. Higher P in feedstuffs caused significant negative interferences for N digestibility. IR of nutrient content in carp faeces was estimated at 0.5–1.7% N and 0.4–0.9% P. Considering the metabolic losses, the carp excreta have an 'eutrophic' N:P ratio (2.1:1–5.8:1). Eutrophication potential from feeding seems linked to P digestibility followed by bad protein profile of diets. While brewery wastes, microbial protein and natural prey offer high P digestibility (75–90%), large knowledge gaps still exist in P digestibility of various ingredients. Thermal processing does not always improve P digestibility; acidic pre‐incubation with phytases (optimum: 1500–2000 IU kg −1 feed) is worth exploring. Under semi‐intensive system, digestible 'supplementary' nutrients (N: 3.3–4.9%, P: 0.2–0.5%; even lower) can support at least 0.6–1.2 thermal growth coefficient (reasonable growth) and be ecologically relevant. We further considered validity of data within experimental conditions; effects on N/P utilization; non‐faecal losses (IRs 17–59% of N intake; 9–18% of P intake); and controversies over eutrophication. Recent eutrophication of carp fishponds might have been rather 'management‐driven' than carp's biological limitations. Ameliorative measures are outlined.